In vitro and in vivo pharmacological characterization of nociceptin/orphanin FQ tetrabranched derivatives. (September 2014) - Rizzi, A; Malfacini, D; Cerlesi, M C; Ruzza, C; Marzola, E; Bird, M F; Rowbotham, D J; Salvadori, S; Guerrini, R; Lambert, D G; Calo, G
<x xml:space="preserve">Abstract</x> Background and Purpose An innovative chemical approach, named peptide welding technology (PWT), allows the synthesis of multibranched peptides with extraordinary high yield, purity and reproducibility. With this approach, three different tetrabranched derivatives of nociceptin/orphanin FQ (N/OFQ) have been synthesized and named PWT1‐N/OFQ, PWT2‐N/OFQ and PWT3‐N/OFQ. In the present study we investigated the in vitro and in vivo pharmacological profile of PWT N/OFQ derivatives and compared their actions with those of the naturally occurring peptide. Experimental Approach The following in vitro assays were used: receptor and [35S]‐GTPγS binding, calcium mobilization in cells expressing the human N/OFQ peptide (NOP) receptor, or classical opioid receptors and chimeric G proteins, electrically stimulated mouse vas deferens bioassay. In vivo experiments were performed; locomotor activity was measured in normal mice and in animals with the NOP receptor gene knocked out [NOP(−/−)]. Key Results In vitro PWT derivatives of N/OFQ behaved as high affinity potent and rather selective full agonists at human recombinant and animal native NOP receptors. In vivo PWT derivatives mimicked the inhibitory effects exerted by the natural peptide on locomotor activity showing 40‐fold higher potency and extremely longer lasting action. The effects of PWT2‐N/OFQ were no longer evident in NOP(−/−) mice. Conclusions and Implications The results showed that the PWT can be successfully applied to the peptide sequence of N/OFQ to generate tetrabranched derivatives characterized by a pharmacological profile similar to the native peptide and associated with a higher potency and marked prolongation of action in vivo.